(untitled) (Педагогіка вищої та середньої школи, 2006)
The article deals with the questions of forming of system of mode and methods in a historical education as a necessity that is naturally stipulated by the condition of reformation and closing to the European and world standards. Some aspects of practical realization of this task are revealed.